Analysis of motivational climate and social interactions in physical education classes in secondary school - Flores Piñero, María del Carmen; Valdivia Moral, Pedro Ángel; González Hernández, Juan (SPORT TK-EuroAmerican Journal of Sport Sciences, 2023)
The motivational climate refers to the set of signals from the PE class environment, which can be implicating the ego or the task. The objective of this research is to know the motivational climate and its elements such as approach, avoidance, ego and task, prosocial behaviors and aggressive behaviors of high school students in PE classes. This study has been carried out with a cross-sectional and intentional methodology, in a sample of Compulsory Secondary Education students (N=84) in educational centers in Andalucia and the Canary Islands. The results concluded that the motivational climate generated by the PE teacher and that students may or may not perceive in their classes, has a definite tendency towards Approach Motivational Climate and Avoidance Motivational Climate, both with 40.5%. The results also confirm that the students present prosocial behaviors and do not present aggressive behaviours.